Rural crime in developing countries: theoretical framework, empirical findings, research needs - Grote, Ulrike (ZEF working paper series)
Anecdotal evidence and selected information from the International Crime Victims Survey suggest that crime is higher in developing countries than in developed countries and that there are regionally big differences. Explanations and solutions to the persistence and prevalence of rural crime in many developing countries are needed as rural crime undermines sustainable development to a large extent and may even affect social cohesiveness in rural communities. This discussion paper therefore calls for research which helps to shed light on this phenomenon in support of improved policies. For this, representative and good-quality data is needed. It is suggested to disentangle the complex research topic and allow for a more systematic approach by focusing on a certain type of crime. Research on most of these types is very selective and scarce. As mentioned, data is almost nonexistent and evidence on individual types is largely missing. The routine activity approach is suggested as a conceptual framework for further analysis. The paper concludes that research and policy design should focus on how to reduce opportunities to commit a crime in rural areas in developing countries in order to reduce environmental and social costs of crime, promote sustainable development and improve rural livelihoods of the often deprived and poor in rural areas in developing countries.